Analisis Faktor yang Mempengaruhi Keterampilan Berbicara Selama Proses Pembelajaran Mahasiswa - Azza Dhifa Zayyan Hanifa; Heri Saptadi Ismanto; Agus Setiawan (Universitas Muria Kudus, 2022)
The low speaking skills possessed by students such as, insecurity and nervousness when dealing with many people, this makes students stammer so that they often say the word